How do Stress Coping and Religiosity Influence the Subjective Well-being of Online Motorcycle Partners? - Nurani, Garis; Utami, Lufiana Harnany (Jurnal Psikologi Islam dan Budaya, 2024)
The subjective well-being is crucial for online motorcycle partners in enhancing happiness at work, maximizing work motivation, and achieving life satisfaction. This research aims to study about stress coping and religiosity affect on subjective well-being of online motorcycle taxi partners. Having quantitative correlational method, the research involved 349 Grab and Gojek motorcycle taxi partners scattered across Indonesia as research subjects. Four istruments were used: the Satisfaction with Life Scale (SWLS), Scale of Positive and Negative Experience (SPANE), Brief Cope scale, and Centrality Religiosity Scale (CRS). Data analyse used multiple linear regression. The research found that both stress coping and religiosity have affceted subjective well-being of online motorcycle taxi partners, both partially and simultaneously. These two variables are essential for online motorcycle taxi partners in carrying out their profession to achieve good subjective well-being.